2017
DOI: 10.1002/lno.10677
|View full text |Cite
|
Sign up to set email alerts
|

Major fertilization sources and mechanisms for Mediterranean Sea coastal ecosystems

Abstract: The Mediterranean Sea is considered an oligotrophic basin with a few biological production hotspots. Some of these productive regions are under the influence of large rivers' discharges and have been described to suffer from eutrophication indications. In order to quantify the impact of the river-borne inorganic nutrients on the pelagic production levels and bottom oxygen conditions in the northern coast of the Mediterranean Sea, two hindcast simulations using a coupled hydrodynamic-biogeochemical model are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 71 publications
(106 reference statements)
2
22
0
1
Order By: Relevance
“…Eutrophication is in evidence in small coastal lagoons and bays affected by intense human activity (Karydis and Kitsiou, 2012). In more open waters, nutrients supplied by rivers are responsible for a large fraction of the pelagic primary production and for bottom hypoxic area only in the Adriatic and Aegean basins (Macias et al, 2017).…”
Section: Mediterranean Seamentioning
confidence: 99%
“…Eutrophication is in evidence in small coastal lagoons and bays affected by intense human activity (Karydis and Kitsiou, 2012). In more open waters, nutrients supplied by rivers are responsible for a large fraction of the pelagic primary production and for bottom hypoxic area only in the Adriatic and Aegean basins (Macias et al, 2017).…”
Section: Mediterranean Seamentioning
confidence: 99%
“…As an alternative approach, coupled physical-biogeochemical models have been used for the reconstruction 45 of pristine conditions of the Baltic Sea (Schernewski & Neumann, 2005) and the North Sea (Lancelot et al, 2014;Desmit et al, 2015). In a wider context of the eutrophication problem, such models have been successfully applied to a number of systems, including, but not limited to; the North Sea (Lenhart et al, 2010), the Baltic Sea (Neumann et al, 2002), the Black Sea (Salihoglu et al, 2017), the Mediterrenean Sea (Macias & Stips, 2017) and the Gulf of Mexico (Laurent et al, 2012). Coupled physical-biogeochemical models do not 50 only provide insight into how the ecosystems may behave under different environmental forcing, but they also serve in gaining understanding of the specific mechanisms responsible for the observed and predicted phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these differences have been evidenced within the RADMED area by means of the use of long time series of phyto and zooplankton data. One of the mechanisms that can inject nutrients to the photic layer, increasing the primary production and reducing the oligotrophy of the Mediterranean waters, is the existence of frontal systems and eddies [51,54,55]. The results of the present work show that diatoms are the most abundant group in the phytoplanktonic community in the westernmost stations of the Alboran Sea, not only in winter or spring, but throughout the whole year.…”
Section: Discussionmentioning
confidence: 59%
“…Nevertheless, many works have shown that this general patternmay undergoimportant modifications as several mechanisms can fertilize the upper layer of the sea, altering the oligotrophy of the Mediterranean waters and creating mesotrophic conditions [48,51]. Other works have shown that differentiated regions can be established in the Mediterranean Sea according to the concentrations of chlorophyll at the sea surface and along the water column,and the timing of the phytoplanktonic bloom [52,53].…”
Section: Discussionmentioning
confidence: 99%